Multi-channel PMMA microfluidic biosensor with integrated IDUAs for electrochemical detection - Wongkaew, Nongnoot (2013)
A novel multi-channel poly(methyl methacrylate) (PMMA) microfluidic biosensor with interdigitated ultramicroelectrode arrays (IDUAs) for electrochemical detection was developed. The focus of the development was a simple fabrication procedure and the realization of a reliable large IDUA that can provide detection simultaneously to several microchannels. As proof of concept, five microchannels are positioned over a large single IDUA where the channels are parallel with the length of electrode finger. The IDUAs were fabricated on the PMMA cover piece and bonded to a PMMA substrate containing the microfluidic channels using UV/ozone-assisted thermal bonding. Conditions of device fabrication were optimized realizing a rugged large IDUA within a bonded PMMA device. Gold adhesion to the PMMA, protective coatings and pressure during bonding were optimized. Its electrochemical performance was studied using amperometric detection of potassium ferri and ferro hexacyanide. Cumulative signals within the same chip showed very good linearity over a range of 0 - 38 μM (R(2) = 0.98) and a limit of detection of 3.48 μM. The bonding of the device was optimized so that no cross-talk between the channels was observed which otherwise would have resulted in unreliable electrochemical responses. The highly reproducible signals achieved were comparable to those obtained with separate single-channel devices. Subsequently, the multi-channel microfluidic chip was applied to a model bioanalytical detection strategy, i.e. the quantification of specific nucleic acid sequences using a sandwich approach. Here probe-coated paramagnetic beads and probe-tagged liposomes entrapping ferri/ferro hexacyanide as the redox marker were used to bind to a single stranded DNA sequence. Flow rates of the non-ionic detergent n-octyl-β-D-glucopyranoside (OG) for liposome lysis were optimized and the detection of the target sequences was carried out coulometrically within 250 s and with a limit of detection of 12.5 μM. The robustness of the design and the reliability of the results obtained in comparison to previously published single-channel designs suggest that the multi-channel device offers an excellent opportunity for bioanalytical applications that require multi-analyte detection and high throughput assays.